Citizen Journalism and Online Community Media: A Case Study of pwmu.co - Sukmono, Filosa Gita; Junaedi, Fajar (Universitas Semarang, 2019)
One of the most prominent online community media in Muhammadiyah is pwmu.co (https://pwmu.co/) that published by the Regional Office of Muhammadiyah (PWM) East Java. This article departs from an interest of the writing team to find out how citizen journalism-based media management works in the online community media, especially pwmu.co. This study itself uses a case study method by collecting data using in-depth interviews, then selecting informants using purposive sampling or criterion-based selection. In this study, informants were pwmu.co editors, while observations were made by looking carefully at the pwmu.co editorial room. The result demonstrates that community media management executed by pwmu.co accentuates citizen journalism principles and voluntarily actions to resolve their works relating to collecting news. Journalists and reporters in this community are citizen journalist that comes from Muhammadiyah people and they are trained through a series of the workshop by the editors of pwmu.co.